Carcinogenic and non-carcinogenic human health risk assessment of some vegetables irrigated with wastewater in Jos, Plateau State, Nigeria - Usman Bawa; Ahmad AbdulHameed (Exploration of Foods and Foodomics)
Aim: There is growing concern on the use of contaminated and untreated water from industrial discharge for irrigation during the dry season farming in many parts of northern Nigeria. Industries effluents are among the major sources of heavy metal pollution of water bodies and when used for irrigation could be a source of heavy metal bioaccumulation in crops. This study determined the potential non-carcinogenic and carcinogenic health risks in both children and adults through the consumption of some vegetables irrigated with polluted water in Bassa, Plateau, and Nigeria. Methods: Four vegetable farms that exclusively use untreated industrial effluents were identified and eight commonly consumed vegetables were sampled for heavy metal analysis using atomic absorption spectrometry. The metals of interest were Cd, Pb, Cr, Cu, and Zn. Results: Concentrations of Cd, Pb, and Cr in all the vegetables exceeded the WHO’s permissible limits while Cu and Zn did not. Mean heavy metals in the vegetables ranged from 26.87–33.50 mg/kg (Cd), 4.17–10.90 mg/kg (Pb), 27.00–38.67 mg/kg (Cr), 10.60–24.38 mg/kg (Cu), and 1.77–3.42 mg/kg (Zn). Estimated daily intake (EDI) for Cd and Pb for both children and adults exceeded the oral risk-free dose (RFD) set by US-EPA. However, the EDI of Cu in children exceeds the RFD while the EDI of adults did not exceed RFD. Consumption of all the metal-contaminated vegetables posed a potential non cancer risk hazard index (HI ≥ 1) in both children and adults while the target cancer risks (TCR) were due to ingestion of Cd and Cr in the vegetables with TCR values above 1 × 10–4. Conclusions: This study found that adults and children population in this area are susceptible to non cancer and cancer health risks from the consumption of all the studied vegetables. Screening of industrial effluent should be prioritized and enforced to avoid crop heavy metal bioaccumulation.